2021
DOI: 10.4102/phcfm.v13i1.2924
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, phenomenology and personality characteristics of premenstrual dysphoric disorder among female students at Zagazig University, Egypt

Abstract: Background: Premenstrual dysphoric disorder (PMDD) is a female psychiatric disorder affecting the behaviour, cognitive abilities, mental health status and academic performance of female students. It includes: mood symptoms, behaviour symptoms and physical symptoms.Aim: To assess phenomenology, measure the prevalence of PMDD among university students and assess the relationship between PMDD and socio-demographic and personality characteristics.Setting: This study was conducted at Zagazig University, Sharqia Gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…In a study of 200 university students in Nigeria, it was reported that 85.5% experienced PMS, and the most frequent symptoms were found to be lower abdominal pain, oedema/spots on the face, sensitivity/heaviness in the breasts, depression/tension, and fatigue (13). Although there are differences in the ranking of symptoms in previous studies, it can be seen that the health of young girls and women is negatively affected by PMS (14). A study was conducted in the USA between 15 April and 25 June 2020 of patients with a positive RT-PCR test for SARS-CoV-2 infection who were treated as outpatients, and the most commonly reported symptoms were fatigue (71%), cough (61%), and headache (61%) (15).…”
Section: Discussionmentioning
confidence: 97%
“…In a study of 200 university students in Nigeria, it was reported that 85.5% experienced PMS, and the most frequent symptoms were found to be lower abdominal pain, oedema/spots on the face, sensitivity/heaviness in the breasts, depression/tension, and fatigue (13). Although there are differences in the ranking of symptoms in previous studies, it can be seen that the health of young girls and women is negatively affected by PMS (14). A study was conducted in the USA between 15 April and 25 June 2020 of patients with a positive RT-PCR test for SARS-CoV-2 infection who were treated as outpatients, and the most commonly reported symptoms were fatigue (71%), cough (61%), and headache (61%) (15).…”
Section: Discussionmentioning
confidence: 97%
“…The primary types of symptoms include behavioural, psychological, and physical manifestations [ 23 ]. Affective symptoms may persist for several days to two weeks, with a symptom-free period typically preceding ovulation [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, numerous studies have evaluated childhood body size and premenstrual disorders in young adulthood (36), comorbid bipolar disorder (37), prevalence, and associated factors among different groups (38). For instance, studies showed that the prevalence of PMS among Academics at a University in Midwest Brazil was 46.9% (38), and 21.1% for university students (39), which are higher than ever before. Moreover, risk factors for PMS/PMDD include childhood abuse and neglect (40), childhood maltreatment (41), and perinatal depression (42), among others.…”
Section: Epidemiology For Prevalence and Risk Factorsmentioning
confidence: 99%